Metric sex estimation from the postcranial skeleton for the Colombian population. (May 2016) - Moore, Megan K.; DiGangi, Elizabeth A.; Niño Ruíz, Francis Paola; Hidalgo Davila, Oscar Joaquín; Sanabria Medina, César
Highlights: First postcranial metric sex standards presented for a Colombian population. Results include uni- and multivariate equations to apply to varied forensic cases. Best univariate measurement is scapula height; best multivariate bone is scapula. Results similar to North American Hispanic sample, though some variation. Abstract: This research explores the best univariate and multivariate indicators for sex estimation using 51 standard osteometric measurements of all six major postcranial long bones, bones of the shoulder girdle, pelvic girdle, and the calcaneus from a modern, Colombian skeletal collection. The hypotheses being tested are (1) that postcrania will yield accurate sex classification rates and (2) the shoulder girdle will demonstrate the highest discrimination, based on results from previous research. The sample consists of 134 individuals (50 females, 84 males) between the ages of 19 and 93 with a mean age of 47 years. The sample is from the Colombian Skeletal Collection, consisting of skeletons from cemeteries in Bogotá, with recent years of death. The methods include univariate and multivariate discriminant function analysis (DFA). The results for this sample indicate the same general pattern of univariate classification effectiveness as found in research on North Americans; however, here the humerus performs better than the distal femur and proximal tibia as demonstrated in some North American samples. The cross-validated percent correct univariate classification for the postcranial elements ranges from 64.8% to 86.1% ( p < 0.05). The highest univariate classification rates were for the scapular height (86.1%) and the humeral head diameter (86.0%). The highest multivariate classification rates are with the scapula (93.5%), os coxa (92.0%), clavicle (89.9%), humerus (89.1%), and ulna (89.1%). This study provides sectioning points to easily estimate sex using Colombian population-specific formulae. This research aids in forensic individuation, as the long bones of the postcranial elements are relatively resistant to taphonomic processes. Furthermore, the ability to achieve such a high degree of success from a single bone is preferable for the fast-paced forensic anthropology laboratories in Colombia that process hundreds to thousands of cases each year. This research plays an important role in the development of population standards in Colombia and South America and provides a robust method that can withstand courtroom scrutiny.